Rozwój technologii informacyjnych szansą czy zagrożeniem dla społeczeństwa obywatelskiego? - Radziszewski, Mateusz (Eastern Review, 2018)
The political participation of citizens is a fundamental element of a democratic system and guarantees the realization of democratic values.An important element of participation is the use of information technologies in this process. The first part of the article contains the worldwide research review of civil participation and the use of information technologies in the communication between the government and citizens.The next part is the analysis of the use of information technologies in a participatory budgeting in Lodz and Poznan in 2014 and 2015. The aim of this research is to find quantitative and qualitative dimension of civil participation in the virtual world.My research will use Robert Putnam’s conception of social capital and D.Easton’s „Systems Analysis of Politics”.The hypotheses are: H1: information technologies are an important part of civil participation process, H2: Use of information technologies has no influence on qualitative dimension of civil participation.